Active SOI Optical Ring Resonator Based on Free Carrier Injection - Mardiana, Bidin; Haroon, Hazura; Hanim, Abdul Razak; Sahbudin, Saari; Menon, P.S; Abdullah, H. (Trans Tech Publications Inc, 2012)
This paper highlights the study of the free carrier injection effect on the active SOI optical ring resonator. The effect of the free carrier injection on optical ring resonator was evaluated by varying the p+ and n+ doping concentrations. The device performances are predicted by using numerical modelling software of the 2D SILVACO and Finite Difference Time Domain method simulation software RSOFT. The results show the refractive index change increases as the p+ and n+ doping concentrations is getting higher. A shift in resonant wavelength of around 2 nm was predicted at 5x1019 cm3 p+ and n+ doping concentrations with 5.8x10-3 refractive index change. It is also shown that 8.2dB change of the output response obtained through the output.